The Construction manager - Royer, King (Englewood Cliffs, New Jersey : Prentice-Hall, 1974)
My earlier Desk Book for Construction Superintendents is directed to new super-intendents, explaining procedures followed by most construction firms. I here extend that explanation to the responsibility of the person initiating estimates, purchasing, and cost control. Small contractors do this personally; in medium-size firms, a project manager is designated, and in larger companies the project manager is assisted by accounting, estimating, scheduling, or other departments.
Chapter 1. The Construction Firm -- Chapter 2. The Construction Project -- Chapter 3. Estimating -- Chapter 4. Construction Contracts -- Chapter 5. Purchasing -- Chapter 6. Accounting -- Chapter 7. Planning and Scheduling -- Chapter 8. Labor Unions -- Chapter 9. Bibliography.
Includes index.
Keywords: CONSTRUCTION INDUSTRY